Sound Of Nangqên - Jiayue Cecilia Wu (Journal of the Association for Technology in Music Instruction, 2025)
Tape Piece is part of a series of single-sound-source daydream pieces, where a solitary object or family of objects is repurposed to create an otherworldly soundscape. This work uses tape–masking, scotch, aluminum, packing, and duct–sometimes recognizable, and sometimes heavily processed. The familiar is juxtaposed with the fresh, and what starts out with unrolling and tearing quickly unravels as sounds evocative of gunfire, of bombs and explosions, and of Geiger counters suggesting the downfall of civilization. New creatures emerge throughout, each trying to find their place in a world that has come unglued.
Keywords: composition